PENGARUH LOKASI DAN FASILITAS TERHADAP KEPUASAN PELANGGAN LIMASAN KAFE KARAWANG - Setiawan, Rido; Kosasih, Kosasih; Sudrajat, Ajat (Buletin Studi Ekonomi, 2019)
Abstract: The Effect of Location and Facilities on Limasan Cafe Karawang Customer Satisfaction. The problems of this study are (1) how big is the relationship between location and facilities, (2) how big is the partial influence of location and facilities on customer satisfaction, (3) how big is the simultaneous influence of location and facilities on customer satisfaction. This research uses a descriptive, verification approach. Samples obtained were 343 respondents who were consumers of Limasan Karawang cafes using incidental sampling techniques, data analysis used in this study was the validity test, reliability test, normality test, path analysis, and hypothesis testing. Based on the results of the study showed the criteria agreed on the location obtained an average of 1319 and on the facilities obtained an average of 1272. While the Criteria agreed on customer satisfaction obtained an average of 1363. The results showed the location and facilities have a strong relationship, amounting to 0.773 . Location has a direct influence of 39.5% on customer satisfaction. As for the facility has a direct influence of 4% on customer satisfaction and both indirect effects on customer satisfaction of 9.7%. So it can be explained that location variables are more dominant in influencing customer satisfaction and Limasan Karawang cafes are advised to pay more attention to facility variables for customer satisfaction convenience.